2015
DOI: 10.1002/2014jb011573
|View full text |Cite
|
Sign up to set email alerts
|

Crust and subduction zone structure of Southwestern Mexico

Abstract: Southwestern Mexico is a region of complex active tectonics with subduction of the young Rivera and Cocos plates to the south and widespread magmatism and rifting in the continental interior. Here we use receiver function analysis on data recorded by a 50 station temporary deployment of seismometers known as the MARS (MApping the Rivera Subduction zone) array to investigate crustal structure as well as the nature of the subduction interface near the coast. The array was deployed in the Mexican states of Jalisc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Based on the obtained results and other available information, we propose a scenario of magma feeding, schematically shown in Figure . According to the estimates by Suhardja et al () based on the receiver function analysis, the Moho depth beneath the CVC is about 40–42 km. Thus, the velocity structures observed at 60‐km depth correspond to the uppermost mantle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the obtained results and other available information, we propose a scenario of magma feeding, schematically shown in Figure . According to the estimates by Suhardja et al () based on the receiver function analysis, the Moho depth beneath the CVC is about 40–42 km. Thus, the velocity structures observed at 60‐km depth correspond to the uppermost mantle.…”
Section: Discussionmentioning
confidence: 99%
“…SKS splitting analysis has revealed azimuthal anisotropy, which has provided evidence for slab tear beneath the CR (Soto et al, ). Suhardja et al () derived information about the Moho depth beneath the south‐western Mexico using receiver function analysis. Regional heterogeneities beneath the Rivera region were also investigated with the use of ambient noise tomography (Castellanos et al, ; Spica et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The current rift is at a late stage 1 (based on observations from Acambay graben; Figure and Table ). Most of the deformation is still accommodated by the rift‐bounding faults, compared to faults at the graben axis (e.g., Langridge et al, , ; Suter et al, ; Ortuño et al, ), and the crust is still thick (40–50 km) (Suhardja et al, ; Urrutia‐Fucugauchi & Flores‐Ruiz, ). However, coeval volcanism and faulting in the graben axis (Sunye‐Puchol et al, ; Suter et al, ) suggests that extension is also partially accommodated by dike intrusion, indicating that the rift is evolving toward stage 2.…”
Section: Discussionmentioning
confidence: 99%
“…Coseismic and postseismic deformation of the 1995 M w 8.0 Jalisco earthquake. Depth below sea level of the megathrust, based onPardo and Suarez (1995) andSuhardja et al (2015), is contoured at 10-km intervals (light violet dashed lines). (a) Observed(Melbourne et al, 1997) and model-predicted horizontal coseismic displacements using the shown slip distribution.…”
mentioning
confidence: 99%